Value Identification on The Internal Governance Structure of A Selected Private University in China - Liu, Jingmei (Pacific International Journal, 2024)
This study investigated the relationship between value identification and governance structures at a private Chinese university. A quantitative correlational research design was utilized. The sample consisted of 313 faculty members from Weifang University, selected through proportionate stratified sampling. A questionnaire measured demographics, value identification, and governance structures. Data were analyzed using correlation, ANOVA, and t-tests. Results showed significant positive correlations between value identification and governance structure subscales. No significant demographic differences emerged except for academic rank affecting value identification. These findings contribute to theory and knowledge on aligning values and governance in higher education. Further research across institutional types is recommended.